2022
DOI: 10.1002/jcph.2120
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis and Related Events Following COVID‐19 Vaccination: A Systematic Review

Abstract: The Coronavirus Disease 2019 (COVID‐19), induced by the SARS CoV‐2 virus, is responsible for a global pandemic following widespread transmission and death. Several vaccines have been developed to counter this public health crisis using both novel and conventional methods. Following approval based on promising efficacy and safety data, the AstraZeneca, Janssen, Moderna, Pfizer/BioNTech, and SinoVac vaccines have been administered globally among different populations with various reported side effects. Reports o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
(172 reference statements)
0
3
0
Order By: Relevance
“…Despite initial concerns of various adverse events stemming from accelerated production and distribution of the various SARS-CoV-2 vaccines [ 66 69 ], they have undoubtedly been the most effective shield against this pandemic [ 70 72 ], estimated to have prevented 20 million deaths in the first year of roll-out alone [ 73 ]. Vaccines were shown to act as a booster in those previously infected by eliciting a similar titer count compared to infection-naïve individuals receiving 2 doses [ 74 , 75 ], while also providing more durable protection in such individuals [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite initial concerns of various adverse events stemming from accelerated production and distribution of the various SARS-CoV-2 vaccines [ 66 69 ], they have undoubtedly been the most effective shield against this pandemic [ 70 72 ], estimated to have prevented 20 million deaths in the first year of roll-out alone [ 73 ]. Vaccines were shown to act as a booster in those previously infected by eliciting a similar titer count compared to infection-naïve individuals receiving 2 doses [ 74 , 75 ], while also providing more durable protection in such individuals [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although this has led to the identification of various COVID-19 vaccine candidates, the high and growing demand for the vaccine has become a challenge (Bubar et al, 2021 ). Among these candidates, the vaccines developed by Pfizer-BioNTech, Moderna COVID-19, Oxford-AstraZeneca COVID-19, Sinovac COVID-19, and Johnson & Johnson COVID-19 have received Emergency Use Authorization (EUA) from regulatory bodies in the UK, Europe, USA, China, and India (Acharya et al, 2021 ; Kalinke et al, 2022 ; Mushtaq et al, 2022 ; Paul et al, 2022 ). It has been demonstrated that these vaccines can provide reasonable levels of protection against symptomatic and severe disease with two doses administered 3–4 weeks apart (Polack et al, 2020 ; Baden et al, 2021 ; Dagan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The authors [6] conducted a systematic search of the literature using PubMed, Embase, Scopus, Web of Science, Science Direct, MedRxiv, and Lens.org databases, which contained studies reporting anaphylaxis after vaccine injection. The conducted systematic review included 41 studies which reported anaphylaxis.…”
mentioning
confidence: 99%